2019
DOI: 10.2147/ijn.s203911
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparisons of in vitro Fick’s first law, lipolysis, and in vivo rat models for oral absorption on BCS II drugs in SNEDDS</p>

Abstract: Purpose The objective of this study was to compare the in vitro Fick’s first law, in vitro lipolysis, and in vivo rat assays for oral absorption of Biopharmaceutical Classification Systems Class II (BCS II) drugs in self-nanoemulsifying drug delivery system (SNEDDS), and studied drugs and oils properties effects on the absorption. Methods The transport abilities of griseofulvin (GRI), phenytoin (PHE), indomethacin (IND), and ketoprofen (KET) in saturated water solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Excipients selection was mainly based on their ability to solubilize the highest amounts of the AZM. The impact of lipids classes as long carbon chain triglycerides (LCT) and medium carbon chain triglycerides (MCT) was observed, as such differences in carbon chain lengths were reported to have an influence on drug solubilization potential and the ability to facilitate the emulsification process [38,39]. Extra attention was given to include excipients with previously reported abilities to loosen the cellular TJ for the possibility of enhancing the drug paracellular route diffusion.…”
mentioning
confidence: 99%
“…Excipients selection was mainly based on their ability to solubilize the highest amounts of the AZM. The impact of lipids classes as long carbon chain triglycerides (LCT) and medium carbon chain triglycerides (MCT) was observed, as such differences in carbon chain lengths were reported to have an influence on drug solubilization potential and the ability to facilitate the emulsification process [38,39]. Extra attention was given to include excipients with previously reported abilities to loosen the cellular TJ for the possibility of enhancing the drug paracellular route diffusion.…”
mentioning
confidence: 99%
“…After lipolysis, RAL was rapidly released and the chylomicrons were formed by lipolytic products of LNE and then uptake into the blood or lymphatic system, resulting in a higher C max than those of SUSP and NNE. 15,38 In contrast, the RAL encapsulated in NNE was slowly released and resulted in the lower C max . Although no evident difference between the oral bioavailability of NNE and LNE in rats (Table 3), the bioavailability of NNE in pigs was significantly higher than that of LNE (Table 4).…”
Section: The In Vivo Absorption Of Ral-nnementioning
confidence: 99%
“…32 Furthermore, the intermolecular forces of the ionic bond between RAL and LA were enhanced, resulting in smaller globule sizes. 15,33 Although RAL was most soluble in ethanol, which could efficiently improve its emulsification efficiency, the weight ratio of ethanol in the pre-NE was limited to 10%-20% as ethanol did not retain its solubilization capacity after dispersion in an aqueous system because of its water solubility, which may lead to drug precipitation. 34,35 Therefore, we identified that IP:LA (1:2, w/w), Cremophor RH40, and ethanol in a 5:3:2 weight ratio in pre -NNE was used to prepare the optimal RAL-NNE.…”
Section: Ral-nne Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…where the flux (J) of a drug through the GI barrier wall, which is defined as dM, the cumulative transport mass during dt, depends on the diffusion area (S), permeability coefficient (P) of the drug, and the drug concentration (C) in the GI lumen (assuming sink conditions) [45]. From this equation, it can be estimated that increasing the drug solubility can improve absorption of a poorly water-soluble drug.…”
Section: Increase In Absorption By Supersaturation In the Gitmentioning
confidence: 99%